Global drylands with country boundaries - Getahun, Yasin; Flintan, Fiona E. (International Livestock Research Institute, 2018)
This map shows global aridity classes mapped against country boundaries providing approximate areas of drylands per country. Aridity zones were derived from an Aridity Index (AI) which is calculated as the ratio of precipition to potential evapotranspiration. Zones included in this dataset are: hyperarid, arid, semiarid, and dry subhumid.These are in accordance with the United Nations Convention to Combat Desertification (UNCCD) definition of Drylands and prevously mapped by UNEP-WCMC 2007. Country boundaries were taken from ESRI 2016.